Renal impairment may indicate postoperative low vision in young patients with proliferative diabetic retinopathy undergoing vitrectomy - Zheng, Xiaorong; Feng, Lin; Xing, Chen; Wang, Junlan; Zhao, Wei; Zhang, Fengmei (Frontiers in Endocrinology, 2024)
Objective To innovatively evaluate the impact of renal impairment in young work age patients with proliferative diabetic retinopathy (PDR) on their visuality after vitrectomy. Methods To find out whether it is possible to better predict the improvement of visual acuity after vitrectomy in working-age people without adding additional preoperative testing. In view of the fact that diabetic retinopathy and diabetic nephropathy are common diabetic complications of microvascular damage, it is considered whether preoperative renal function can be used as this evaluation index. This paper studies the design under this theme. This retrospective study included 306 patients (306 eyes) diagnosed with PDR and undergoing vitrectomy in our hospital from January 2016 to June 2023. Relevant baseline data were collected, including age, history of kidney disease and clinical laboratory test results. According to the International Standard Logarithmic Visual Acuity Checklist, the best corrected visual acuity was tested on the first day of admission and one month after surgery, and the difference between the two was subtracted. A difference >0 was defined as “vision improved”. Patients were classified as vision-improved group (n=245) and non-improved group (n=61). The differences in baseline serum urea nitrogen, creatinine, uric acid, Cystatin C, estimated glomerular filtration rate (eGFR) and urine protein distribution between the two groups were statistically analyzed, binary regression analysis was performed for meaningful parameters, and random forest model ranked the characteristics in importance. Results 1.A higher level of serum cystatin C [1.02(0.80,1.48) mg/L vs 0.86(0.67,1.12) mg/L, P<0.001] and a lower eGFR [82.3(50.33, 115.11) ml/(min/1.73m²) vs 107.69(73.9, 126.01) ml/(min/1.73m²), P=0.002] appeared in the non-(vision-)improved group compared with the vision-improved group. 2. The occurrence of preoperation proteinuria history of nephropathy take a larger proportion in non-improved group. 3. Univariate regression analysis showed history of nephrology (OR=1.887, P=0.028), preoperative serum urea nitrogen (OR=0.939, P=0.043), cystatin C (Cys-C) concentration (OR=0.75, P=0.024), eGFR (OR=1.011, P=0.003) and proteinuria (OR=3.128, P<0.001) were influencing factors to postoperative visual acuity loss in young working age PDR patients. Excluding other confounding factors, preoperative proteinuria is an independent risk factor for postoperative vision improvement in working-age PDR populations (OR=2.722, P=0.009). 4. The accuracy of the prediction random forst model is 0.81. The model appears to be superior in terms of positive prediction. Conclusion In young work aged PDR patients undergoing vitrectomy, preoperative urine protein can be an independent indicator of postoperative visual loss. Aggressive correction of kidney injury before surgery may help improve postoperative vision in patients with PDR.